Prevalence and Characterization of Escherichia coli from Rectal Swab of Apparently Healthy Cattle in Mymensingh, Bangladesh - Hassan, Jayedul; Parvej, Md Shafiullah; Rahman, Md Bahanur; Khan, Md Shahidur Rahman; Rahman, Md Tanvir; Kamal, Tazrin; Nazir, KHM Nazmul Hussain (Microbes and Health, 2014)
Cattle are considered as one of the sources of pathogenic E. coli worldwide. The present study was designed to determine the prevalence and identification of the E. coli isolated from rectal swab of apparently healthy cattle in Mymensingh, Bangladesh. A total of 128 rectal swab samples were assessed by cultural, morphological and biochemical examination followed by Polymerase Chain Reaction (PCR) using primers ECO-1 and ECO-2 that are specific for E. coli 16S rRNA gene. Data obtained from this study were analyzed based on the age, sex, breed and management systems of cattle. This study revealed a 75% prevalence of E. coli in the rectal swab of cattle. Higher prevalence was found in female cattle of unorganized farming systems, and in cattle ?3 years of age. From this study, it may be concluded that, irrespective of age, sex, breed and management system, E. coli is prevailing in the rectal swab of apparently healthy cattle. DOI: http://dx.doi.org/10.3329/mh.v3i1.19775 Microbes and Health, June 2014. 3(1): 12-14